2015
DOI: 10.2134/agronj14.0276
|View full text |Cite
|
Sign up to set email alerts
|

Maize–Velvet Bean Rotation in Summer and Winter Milpas: A Greener Technology

Abstract: In Central America, the traditional cropping system milpa de año (summer season) and tornamilpa (winter season) were compared over 3 yr (2007–2009). Our experimental objectives were to measure the performance of a maize (Zea mays L.)–velvet bean [Mucuna pruriens (L.) DC. subsp. utilis (Wight) Burck] milpa system throughout the summer and winter cultivation, to detect any problems associated with velvet bean use, and to determine the contribution of this tropical legume to soil fertility and maize productivity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…When evaluating elite maize variants in six regions under multiple conditions of abiotic stress, Trachsel et al (2016) reached an average yield of 6.2 and 2.15 Mg ha –1 under optimal conditions and drought and N deficiency, respectively. The results of this study showed that the traditional mején cultivar yielded 3.3 Mg ha –1 , a production that was significantly higher (18.5%) than that of the improved cultivars (CP‐560, CP‐561, and CP‐562, equivalent to 45–60% of yield under no stress conditions; Mejía‐Conteras and Molina, 2002), but similar to the maize–mucuna rotation agroecosystem practiced in southeastern Mexico and Latin America (Ortiz‐Ceballos et al, 2012, 2015; Pacheco‐Cobos et al, 2015). Also, the traditional mején cultivar reached an average yield higher than the obtained in lowland milpas of the Mexican tropics (Donnet et al, 2017).…”
Section: Discussionmentioning
confidence: 63%
“…When evaluating elite maize variants in six regions under multiple conditions of abiotic stress, Trachsel et al (2016) reached an average yield of 6.2 and 2.15 Mg ha –1 under optimal conditions and drought and N deficiency, respectively. The results of this study showed that the traditional mején cultivar yielded 3.3 Mg ha –1 , a production that was significantly higher (18.5%) than that of the improved cultivars (CP‐560, CP‐561, and CP‐562, equivalent to 45–60% of yield under no stress conditions; Mejía‐Conteras and Molina, 2002), but similar to the maize–mucuna rotation agroecosystem practiced in southeastern Mexico and Latin America (Ortiz‐Ceballos et al, 2012, 2015; Pacheco‐Cobos et al, 2015). Also, the traditional mején cultivar reached an average yield higher than the obtained in lowland milpas of the Mexican tropics (Donnet et al, 2017).…”
Section: Discussionmentioning
confidence: 63%
“…Their economic value is lower than that of beans and they do not produce food, but they can be used for fodder (Ruiz-Vega and Loaeza-Ramıŕez, 2003;Beaupréet al, 2021). Similarly, higher maize yields have been observed after a rotation with mucuna in Las Tuxtlas, Veracruz (Ortiz-Ceballos et al, 2015) and in the Selva de Chiapas Region (Aguilar-Jimeńez et al, 2011).…”
Section: Fertility Managementmentioning
confidence: 99%
“…Las leguminosas en rotación con cereales, a la vez que aportan nitrógeno y fósforo reducen la incidencia de malezas al retardar la aparición y aumento de biotipos de gramíneas como avenilla y ballica 9 , las cuales son resistentes a herbicidas selectivos en cultivos de la misma familia botánica (trigo, avena, cebada, triticale). Por otra parte, las leguminosas, por su cobertura y capacidad alelopática (compuesto químico liberado por una planta sobre el desarrollo y crecimiento de otra planta), evitan que las malezas proliferen, gracias a la secreción de compuestos fenólicos, tanto a nivel radical como producto de la descomposición del rastrojo 25,27,28 . Asimismo, ha sido ampliamente documentado el efecto sobre la incidencia de enfermedades en cereales de invierno.…”
Section: Beneficios a La Salud Del Sistema Agrícolaunclassified